Skating mechanics of change-of-direction manoeuvres in ice hockey players - Fortier, A.; Turcotte, R. A.; Pearsall, D. J. (Sports Biomechanics, 2014)
Ice hockey requires rapid transitions between skating trajectories to effectively navigate about the ice surface. Player performance relates in large part to effective change-of-direction manoeuvres, but little is known about how those skills are performed mechanically and the effect of equipment design on them. The purpose of this study was to observe the kinetics involved in those manoeuvres as well as to compare whether kinetic differences may result between two skate models of varying ankle mobility. Eight subjects with competitive ice hockey playing experience performed rapid lateral (90°) left and right change-of-direction manoeuvres. Kinetic data were collected using force strain gauge transducers on the blade holders of the skates. Significantly greater forces were applied by the outside skate (50-70% body weight, %BW) in comparison to the inside skate (12-24%BW, p < 0.05). Skate model and turn direction had no main effect, though significant mixed interactions between leg side (inside/outside) with skate model or turn direction (p < 0.05) were observed, with a trend for left-turn dominance. This study demonstrates the asymmetric dynamic behaviour inherent in skating change-of-direction tasks.